Continuity of care midwifery care in the preconception period - Rahmadini Faricha Hakim; Sausan Dhinda Amallia; Yulizawati Yulizawati (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Continuity of Care (CoC) midwifery care is a service model that provides comprehensive and continuous care to improve women's health status, particularly starting from the preconception period. The preconception period is a critical phase for identifying health risk factors and preparing women physically and mentally for a healthy pregnancy. Purpose: to describe the implementation of Continuity of Care midwifery services during the preconception period. Method: This study employed a case study design involving four women of reproductive age who were prospective brides. Data were collected through anamnesis, physical examination, observation, and documentation using Varney’s midwifery management and SOAP format. Results: The results showed that one client (25%) experienced Chronic Energy Deficiency (CED), and two clients (50%) were classified as obese based on Body Mass Index assessment. All clients (100%) received preconception counseling, nutritional education, and Tetanus Toxoid (TT) immunization. After receiving continuous midwifery care, there was an improvement in clients’ knowledge regarding preconception health and pregnancy preparation. Conclusion: The implementation of Continuity of Care during the preconception period plays an important role in early detection of risk factors and supports the preparation for a healthy pregnancy.